Acute and Sub-Acute Toxicity Studies of Ethyl Acetate Extract of Roots and Rhizomes of Rheum Webbianum Royle in Wistar Albino Rats - Aneequa Rafiquee; Wajid Mohammad Sheikh; Shazia Javeed; Shafiya Bashir; Mubashir Hussain Masoodi; Majid Shafi; Showkeen Muzamil Bashir; Mohammad Younis Dar; Bilal Ahmad Bhat (Penerbit Hellow Pustaka, 2025)
Rheum webbianum Royle, commonly referred to as Himalayan rhubarb, has been extensively utilized in traditional medicine systems such as Ayurveda and Unani. Despite its traditional and pharmacological significance, comprehensive toxicity studies are necessary to ensure its safety. This study investigates the acute and the sub-acute oral toxicity of the ethyl acetate extract of Rheum webbianum Royle in Wistar rat models. The acute toxicity assessment was performed using female rats, administered a single oral dose of 500 mg/kg and 2500 mg/kg body weight, and observed over 14 days for any toxicological manifestations. Similarly, the sub-acute toxicity study involved the administration of daily oral doses of 200 mg/kg, 400 mg/kg, and 800 mg/kg to both male and female rats for 28 days. Throughout the experimental period, all animals were rigorously monitored for any alterations in behavior, morphology, or physiological functions, as well as for any mortality occurrences. The findings from the treated groups were systematically compared with those of the control group to evaluate potential toxic effects. Body weight was recorded weekly, and on days 15 and 29, all animals were sacrificed for the assessment of organ weights, hematological and biochemical parameters, as well as gross and microscopic pathology. No mortality or notable behavioral alterations were observed in the rats at the administered doses, during the acute and sub-acute oral toxicity evaluations. Consequently, it was established that the median lethal dose (LD50) of the plant extract, exceeds 5000 mg/kg. The biochemical parameters were found to be within normal ranges, and histopathological analysis revealed no evidence of toxicity. This indicates that the extract concentrations used in the study do not exert toxic effects on organs such as the heart, liver, kidneys, and brain. Thus, we can conclude that the root and rhizome extract of Rheum webbianum Royle is non-toxic at high doses over short periods of use. However, further research may be needed for extended use of the extract.